An account on some katydids (Orthoptera: Tettigonioidea) from Panti Forest Reserve in Johor, Peninsular Malaysia - Tan, Ming Kai; Muhammad, Amira Aqilah; Gorochov, Andrei V.; Abdullah, Nurul Ashikin (Zootaxa, 2024)
Recent collection in Panti Forest Reserve in Johor, Peninsular Malaysia offered us the opportunity to better understand the species in southern Malay Peninsula. Two new species and one new genus of Meconematini are described here: Cercoteratura reflexa sp. n. and Platycercotura caricauda gen. et sp. n. We present new locality records for Peracca macritchiensis Tan & Ingrisch, 2014, Viriacca viridis Ingrisch, 1998; Lipotactes (Dialipotactes) maculatus Hebard, 1922; Asiophlugis rete Gorochov, 1998; and Arnobia pilipes tropica Gorochov, 1998, all of which were previously recorded in Pahang (Peninsular Malaysia) and Singapore, suggest that the distribution of these species is continuous between Pahang and Singapore. New locality record for Asiophlugis temasek temasek Gorochov & Tan, 2011, previously known only from Singapore, indicates that this subspecies is no longer endemic to Singapore.